LITERATURE REVIEW: AKUNTABILTAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN SEBAGAI PILAR GOOD GOVERNANCE DI SEKTOR PUBLIK - Nikita Mutia Putri; Muhammad Ramzy Agil Faried; Yuniati Yuniati; Armansyah Armansyah (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the role of accountability and transparency in financial management as key pillars in realizing good governance in the public sector. The research method used is a literature review utilizing secondary data sourced from 20 national scientific articles published in the 2020–2025 period and obtained through Google Scholar searches and the Publish or Perish application. The results of the study indicate that accountability and transparency play a significant role in increasing the effectiveness and efficiency of public sector financial management, strengthening the quality and credibility of financial reports, encouraging public participation in oversight, and increasing public trust in the government. In addition, these two principles function as control mechanisms capable of minimizing irregularities in the financial management of villages and other public sector organizations. However, their implementation still faces various obstacles, such as limited human resources, weak internal control systems, low utilization of information technology, and limited access to information for the public. The conclusion of this study shows that accountability and transparency are important foundations in realizing sustainable good governance, thus requiring strengthening the capacity of the apparatus, increasing information disclosure, and optimizing the oversight system to support more accountable and transparent public sector financial management. Keywords: Accountability, Transparency, Financial Management, Good Governance, Public Sector